Improving Branch Prediction Performance with a Generalized Design for Dynamic Branch Predictors - Lin, W.M.; Madhavaram, R.; Yang, A.-Y. (Informatica)
Improving Branch Prediction Performance with a Generalized Design for Dynamic Branch Predictors